Chronic Kidney Disease and Associated Risk Factors Among Patients with Type-2 Diabetes Mellitus in a Tertiary Care Hospital - Islam, Farrukh; Siddiqui, Hamid Jamal; Khalid, Abeer; Farrukh, Ghazal; Yousaf, Shagufta; Ahmed, Abeera (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of chronic kidney disease and its associated risk factors in patients with type 2 Diabetes Mellitus. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital Malir Cantt, Karachi, from Jan to Jun 2019. Methodology: A total of 203 adult patients with Type 2 Diabetes Mellitus were included in the study after taking informed consent on the justification of inclusion/exclusion criteria. The estimated Glomerular filtration rate was calculated for each patient using Creatinine based chronic kidney disease epidemiology collaboration (CKD-EPI) equation. Chronic kidney disease was defined as decreased glomerular filtration rate of <60 mL/min per 1.73m2. In addition, risk factors for developing chronic kidney disease, including Body Mass Index and blood pressure, were clinically determined. Results: Out of 203 patients with type 2 diabetes mellitus, 65(32%) had Chronic kidney disease. Most of them, 34(52.30%), were in Chronic kidney disease stage 3, while 21(32.30%) were in stages 4 and 10(15.40%) were having stage 5. Increasing age, smoking, female gender and higher body mass index were positively correlated with the development of chronic kidney disease in diabetes patients. Conclusion: Chronic kidney disease is a frequently observed complication in diabetes patients. Early detection and appropriate treatment can help in retarding progression to advanced stages of chronic kidney disease. Regular screening of diabetes patients for chronic kidney disease and associated risk factors is therefore recommended.